Influence of Maternal Pelvis Height and Other Anthropometric Measurements on the Duration of Normal Childbirth in Ugandan Mothers - Munabi, Ian G.; Luboga, Samuel Abilemech; Byamugisha, Josaphat; Luboobi, Livingstone; Mirembe, Florence (Anatomy Journal of Africa, 2017)
In low resource settings, maternal anthropometry may complicate time based monitoring of childbirth. We set out to determine the effect of maternal anthropometry and foetal birth weight on the duration of childbirth. Birth related secondary data from 987 mothers with pregnancies of ≥ 37 weeks, singleton baby and a normal childbirth were obtained. This data was analysed for regression coefficients and Interclass correlations coefficients (ICCs). The mean duration of childbirth was 7.63hours. Each centimetre increase in maternal pelvis height led to a 0.56hours increase for the first stage (P<0.01), 0.05hours reduction for second stage (P<0.01), and 0.46hours increase in total duration of childbirth (p<0.01). For each centimeter increase in maternal height there was a 0.04hours reduction in the first stage (P=0.01) and a 0.005hours increase in second stage (P=0.03). The ICCs with respect to geographical site were 0.40 for stage 1, 0.27 for stage 2 and 0.21 for stage 3. Additional modeling with tribe of mother did not change the ICCs. Maternal pelvis height and maternal height were found to have a significant effect on the duration of the different stages of normal childbirth. Additional study is needed into the public health value of the above measurements in relation to childbirth in these settings.
Keywords: Humans; Anthropometry; Childbirth; Pelvis height